2010
DOI: 10.19030/cier.v3i11.245
|View full text |Cite
|
Sign up to set email alerts
|

The Social Media Affinity Scale: Implications For Education

Abstract: In recent years, males and females have demonstrated fairly equal amounts of internet usage, but females have demonstrated higher usage of social media sites. These observed differences served as the impetus for the current study. A survey was conducted in early 2010 among college students to assess whether differences still occur between males and females, and specifically with regard to social media usage. In order to assess these phenomena, the Social Media Affinity Scale was created and deployed. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 10 publications
4
24
0
1
Order By: Relevance
“…Higher scores indicate a higher social media affinity. The Cronbach's ⍺ was calculated to be .77 by Gerlich et al [21], and a Cronbach's ⍺ value of .73 was found for the internal reliability of this study.…”
Section: Measurements 1) Social Media Affinitysupporting
confidence: 50%
See 1 more Smart Citation
“…Higher scores indicate a higher social media affinity. The Cronbach's ⍺ was calculated to be .77 by Gerlich et al [21], and a Cronbach's ⍺ value of .73 was found for the internal reliability of this study.…”
Section: Measurements 1) Social Media Affinitysupporting
confidence: 50%
“…Social media affinity is defined as a person's fondness for or frequent usage of SM [21]. We used the scale developed and validated by Gerlich et al [21], although some questions (such as item 7 and 12) were modified to fit the target population of this study. Authorization to use the scale was provided by the author.…”
Section: Measurements 1) Social Media Affinitymentioning
confidence: 99%
“…Past studies [12,23] reported that males generally showed more competence and more favorable attitude in using technology. However, recent studies [8,11] indicated that there are no gender differences in social media usage. This means females have fairly similar opportunities to get information from SNS compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used by individuals to perform their daily life activities (Anshari & Alas, 2015). According to scholars, several college students use a smartphone to access information through the internet (Gerlich, Browning, & Westermann, 2010). Like other developed countries, usage of smartphone among youth especially students is rapidly growing in Pakistan.…”
Section: Introductionmentioning
confidence: 99%